2017
DOI: 10.1016/j.rbre.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of pamidronate for osteoporosis treatment in public health care in Brazil

Abstract: The intravenous pamidronate in a group of postmenopausal women with predominant high risk of fracture promoted an isolated gain in the spine BMD, even though, clinical randomized trials are needed to confirm its anti-fracture efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…While a monthly dosage is useful and higher BMD is the goal for countermeasures in flight, a higher incidence of adverse effects should indicate a risk analysis for viability of IBN as an acceptable option. For Pamidronate (PMD), a records analysis of 70 women in Brazil who were treated with PMD for osteoporosis showed a significant gain in BMD in the spinal column, but there was no concurrent gain in BMD of the femur [41]. It was also noted that there was elevated PTH levels in some of the patients which was correlated with lower femoral BMD [41].…”
Section: Pharmacologicmentioning
confidence: 99%
See 2 more Smart Citations
“…While a monthly dosage is useful and higher BMD is the goal for countermeasures in flight, a higher incidence of adverse effects should indicate a risk analysis for viability of IBN as an acceptable option. For Pamidronate (PMD), a records analysis of 70 women in Brazil who were treated with PMD for osteoporosis showed a significant gain in BMD in the spinal column, but there was no concurrent gain in BMD of the femur [41]. It was also noted that there was elevated PTH levels in some of the patients which was correlated with lower femoral BMD [41].…”
Section: Pharmacologicmentioning
confidence: 99%
“…For Pamidronate (PMD), a records analysis of 70 women in Brazil who were treated with PMD for osteoporosis showed a significant gain in BMD in the spinal column, but there was no concurrent gain in BMD of the femur [41]. It was also noted that there was elevated PTH levels in some of the patients which was correlated with lower femoral BMD [41]. Another study showed that in a retrospective cohort of 74 postmenopausal women, a placebo group showed elevated spine, hip, and femur BMD compared to a group treated with PMD [42].…”
Section: Pharmacologicmentioning
confidence: 99%
See 1 more Smart Citation